SLC6A1 Mutation and Ketogenic Diet in Epilepsy With Myoclonic-Atonic Seizures - Palmer, Samantha (Pediatr Neurol, 2016)
BACKGROUND: Epilepsy with myoclonic-atonic seizures, also known as myoclonic-astatic epilepsy or Doose syndrome, has been recently linked to variants in the SLC6A1 gene. Epilepsy with myoclonic-atonic seizures is often refractory to antiepileptic drugs, and the ketogenic diet is known for treating medically intractable seizures, although the mechanism of action is largely unknown. We report a novel SLC6A1 variant in a patient with epilepsy with myoclonic-atonic seizures, analyze its effects, and suggest a mechanism of action for the ketogenic diet. METHODS: We describe a ten-year-old girl with epilepsy with myoclonic-atonic seizures and a de novo SLC6A1 mutation who responded well to the ketogenic diet. She carried a c.491G>A mutation predicted to cause p.Cys164Tyr amino acid change, which was identified using whole exome sequencing and confirmed by Sanger sequencing. High-resolution structural modeling was used to analyze the likely effects of the mutation. RESULTS: The SLC6A1 gene encodes a transporter that removes gamma-aminobutyric acid from the synaptic cleft. Mutations in SLC6A1 are known to disrupt the gamma-aminobutyric acid transporter protein 1, affecting gamma-aminobutyric acid levels and causing seizures. The p.Cys164Tyr variant found in our study has not been previously reported, expanding on the variants linked to epilepsy with myoclonic-atonic seizures. CONCLUSION: A 10-year-old girl with a novel SLC6A1 mutation and epilepsy with myoclonic-atonic seizures had an excellent clinical response to the ketogenic diet. An effect of the diet on gamma-aminobutyric acid reuptake mediated by gamma-aminobutyric acid transporter protein 1 is suggested. A personalized approach to epilepsy with myoclonic-atonic seizures patients carrying SLC6A1 mutation and a relationship between epilepsy with myoclonic-atonic seizures due to SLC6A1 mutations, GABAergic drugs, and the ketogenic diet warrants further exploration.